Cloudebug: A Programmable Online Malware Testbed. - Wang, Chi-Wei; Wang, Chia-Wei; Hsieh, Chu-An; Shieh, Shiuhpyng Winston (Computer (00189162), 2014)
Virtual machines for malware analysis in current cloud-based debugging services are not easily accessible or operable by end users. Cloudebug allows users to operate its VM directly in the cloud.